Simulation Training in Implant Restorative Care for Single-Tooth Sites and Implant Overdenture Prosthetic Rehabilitation - Joseph A. Toljanic; Preetha P. Kanjirath; Ryan R. Vahdani; Gary L. Drahos; Marsha A. Babka (Association of American Medical Colleges, 2016)
Abstract Introduction Current preclinical implant rehabilitation training may lack fidelity to clinical experiences, leaving students less prepared for patient care. A pilot course was created to enhance this fidelity in training. Methods In a lecture format, learners are introduced to treatment planning for single-tooth sites. During hands-on exercises using typodonts within a simulation mannequin head, learners fabricate provisional implant crowns, make open and closed tray impressions, and pour impressions for single-tooth implant crown fabrication. In a benchtop exercise, learners place attachments into complete denture prostheses to attach to implant abutments on a mandibular model. Student performance was evaluated using preestablished assessment rubrics, with students self-assessing their performance using the same rubric parameters. Results Two independent clinical performance assessments and a written multiple-choice assessment were conducted, with all students passing these assessments. After graduation, participants were surveyed as to how well the course prepared them to provide implant restorative care. Over half of the course participants rated the course as valuable to very valuable in preparing them to provide implant rehabilitation to future patients. Nearly all respondents agreed that the course should be offered to current dental students. Discussion Since simulated procedures performed in a mannequin head more closely approximate patient care, this methodology may more effectively advance students to the level of competency in implant rehabilitation. Future course expansion may include treatment of multiple tooth sites, incorporating the mannequin head into the overdenture prosthetics module, and surgical training.